2015
DOI: 10.1016/j.neuron.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Locomotion, Theta Oscillations, and the Speed-Correlated Firing of Hippocampal Neurons Are Controlled by a Medial Septal Glutamatergic Circuit

Abstract: Before the onset of locomotion, the hippocampus undergoes a transition into an activity-state specialized for the processing of spatially related input. This brain-state transition is associated with increased firing rates of CA1 pyramidal neurons and the occurrence of theta oscillations, which both correlate with locomotion velocity. However, the neural circuit by which locomotor activity is linked to hippocampal oscillations and neuronal firing rates is unresolved. Here we reveal a septo-hippocampal circuit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

25
343
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(380 citation statements)
references
References 70 publications
(84 reference statements)
25
343
5
Order By: Relevance
“…As for MS-DBB GABAergic neurons, these neurons have unique connectivity to GABAergic interneurons in the hippocampus and strongly fire phase-locked to theta, suggesting that they play an important role in theta generation (Petsche et al, 1962;Freund and Antal, 1988;Stewart and Fox, 1990;Hangya et al, 2009;Bender et al, 2015). Finally, recent in vivo evidence has shown that activation of glutamatergic neurons in the MS-DBB initiates both theta rhythms and locomotor activity in the head-restrained animal (Fuhrmann et al, 2015). Results from this study suggest that direct glutamatergic MS-DBB projections drive interneurons in the stratum oriens, which in turn influence CA1 pyramidal cell firing.…”
Section: Discussionsupporting
confidence: 50%
“…As for MS-DBB GABAergic neurons, these neurons have unique connectivity to GABAergic interneurons in the hippocampus and strongly fire phase-locked to theta, suggesting that they play an important role in theta generation (Petsche et al, 1962;Freund and Antal, 1988;Stewart and Fox, 1990;Hangya et al, 2009;Bender et al, 2015). Finally, recent in vivo evidence has shown that activation of glutamatergic neurons in the MS-DBB initiates both theta rhythms and locomotor activity in the head-restrained animal (Fuhrmann et al, 2015). Results from this study suggest that direct glutamatergic MS-DBB projections drive interneurons in the stratum oriens, which in turn influence CA1 pyramidal cell firing.…”
Section: Discussionsupporting
confidence: 50%
“…Hippocampal neurons also play an important role in the onset of locomotion and exhibit locomotion velocity-dependent firing with theta oscillation (39). Although untested, glycogen-derived lactate might be a contributor to locomotion-dependent hippocampal firing.…”
Section: Discussionmentioning
confidence: 99%
“…http://dx.doi.org/10.1101/211458 doi: bioRxiv preprint first posted online Oct. 30, 2017; 18,258, p = 0.0277) but nonphasers were more widely distributed (range, [0, 0.199 ( Figure 7B, S, gray) consistent with extensive speed modulation in space-related brain areas 288 (Fuhrmann et al, 2015;Kropff et al, 2015). Sorted matrixes of cell-level data confirmed this 289 pattern and showed an inverse relationship between spatial and speed contributions 290…”
mentioning
confidence: 81%